A facile way via integrating sol–gel and Grignard reaction to prepare siloxane/carbosilane hybridized benzocyclobutene resins with hyperbranched structure, low dielectric constant, and high thermal stability. Issue 36 (6th February 2020) - Li, Xian; Huang, Yawen; Ye, Xu; Fan, Li; Peng, Qiuxia; Hu, Huan; Yang, Junxiao
Abstract: The hybridization of siloxane‐ and carbosilane‐based structures in molecular scale could combine their advantages of high thermal resistance and low dielectric constant. However, the hybridization still remained a big challenge in lacking convenient synthesis method. Herein, in this work, we developed a new method via simultaneous Grignard and sol–gel reactions of (chrolomethyl)trimethoxysilane to directly generate siloxane/carbosilane hybridized oligomers with hyperbranched structure. The oligomers were subsequently functionalized by benzocyclobutene and cured to produce crosslinked resins. As‐resulted resins have low dielectric constant (~2.60) as compared with silica and higher thermal stability compared with polycarbosilane. The integrated high performance and facile preparation for these resins make them potentially used as low dielectric materials in integrating circuits insulating and wave transmitting. Abstract :